Design of Public Kitchen Facilities in Stamplat Village with Design Thinking Approach: Perancangan Fasilitas Dapur Umum di Desa Stamplat dengan Pendekatan Design Thinking - Sarvia, Elty; soesilo, Novi; Aji Pranata, Yosafat; Dharmawan, Ary (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2023)
Stamplat Village is one of the tourist villages that has a public kitchen. Currently, the public kitchen facilities are still inadequate, resulting in a few problems that affect the comfort and productivity of its users. Therefore, this research aims to improve the functionality of kitchen facilities by applying the design thinking method, starting from an in-depth understanding of the problems faced by users to the development of prototypes that can be implemented. The design thinking method was chosen as the main approach to ensure that the solutions produced not only fulfill the functional aspects but can also answer the needs and desires of users. At the beginning of the research, observation, and interview methods were used to collect data from users to understand in detail their difficulties, needs, and expectations regarding kitchen facilities. Observations showed the inconvenience in ingredient preparation, cooking, and washing activities caused by the lack of a worktop. The placement of the stove on the wooden floor caused the wood to be perforated due to the heat from the stove. In addition, the squatting position when washing also causes user discomfort. The lack of storage areas such as cupboards and shelves means that food and kitchen utensils are at risk of being infested by insects and rodents. Furthermore, creative ideas were identified to become design solutions by taking into account the principles of ergonomics. The result of the research is the design of public kitchen facilities consisting of cabinets, shelves, and workbenches.